Combination therapy with saxagliptin and vitamin D for the preservation of β-cell function in adult-onset type 1 diabetes: a multi-center, randomized, controlled trial - Xiang Yan; Xia Li; Bingwen Liu; Jiaqi Huang; Yufei Xiang; Yuhang Hu; Xiaohan Tang; Ziwei Zhang; Gan Huang; Zhiguo Xie; Houde Zhou; Zhenqi Liu; et al. (Signal Transduction and Targeted Therapy, 2023)
Abstract Disease modifying therapies aiming to preserve β-cell function in patients with adult-onset autoimmune type 1 diabetes are lacking. Here, we conducted a multi-centre, randomized, controlled trial to assess the β-cell preservation effects of saxagliptin alone and saxagliptin combined with vitamin D as adjunctive therapies in adult-onset autoimmune type 1 diabetes. In this 3-arm trial, 301 participants were randomly assigned to a 24-month course of the conventional therapy (metformin with or without insulin) or adjunctive saxagliptin or adjunctive saxagliptin plus vitamin D to the conventional therapy. The primary endpoint was the change from baseline to 24 months in the fasting C-peptide. The secondary endpoints included the area under the concentration-time curve (AUC) for C-peptide level in a 2-h mixed-meal tolerance test, glycemic control, total daily insulin use and safety, respectively. The primary endpoint was not achieved in saxagliptin plus vitamin D group (P = 0.18) and saxagliptin group (P = 0.26). However, compared with the conventional therapy, 2-h C-peptide AUC from 24 months to baseline decreased less with saxagliptin plus vitamin D (-276 pmol/L vs. -419 pmol/L; P = 0.01), and not to the same degree with saxagliptin alone (-314 pmol/L; P = 0.14). Notably, for participants with higher glutamic acid decarboxylase antibody (GADA) levels, the decline of β-cell function was much lower in saxagliptin plus vitamin D group than in the conventional therapy group (P = 0.001). Insulin dose was significantly reduced in both active treatment groups than in the conventional therapy group despite all groups having similar glycemic control. In conclusion, the combination of saxagliptin and vitamin D preserves pancreatic β-cell function in adult-onset autoimmune type 1 diabetes, an effect especially efficacious in individuals with higher GADA levels. Our results provide evidence for a novel adjunct to insulin and metformin as potential initial treatment for adult-onset type 1 diabetes. (ClinicalTrials.gov identifier: NCT02407899).